2020
DOI: 10.2147/jpr.s249567
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness of Kinesio Taping on the Management of Knee Osteoarthritis: A Systematic Review of Randomized Controlled Trials</p>

Abstract: The purpose of this review was to summarize the current best evidence for the effectiveness of Kinesio Taping in reducing pain and increasing knee function for patients with knee osteoarthritis. A comprehensive search of literature published between 2014 and 2019 was conducted using the following electronic databases: PubMed, Google Scholar, Physiotherapy Evidence Database (PEDro), Science Direct, and Scopus. Only randomized controlled trials evaluating the effect of Kinesio Taping on knee osteoarthritis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The treatment methods for KOA include mainly surgical treatment, drug treatment, and physical therapy [23][24][25], and drug therapy for KOA comprises mainly nonsteroidal anti-inflammatory drugs and glucosamine [26]. Although the application of these drugs alleviates the pain or improves the activity of KOA patients, the objective adverse reactions and high costs of these drugs are still key problems that need to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment methods for KOA include mainly surgical treatment, drug treatment, and physical therapy [23][24][25], and drug therapy for KOA comprises mainly nonsteroidal anti-inflammatory drugs and glucosamine [26]. Although the application of these drugs alleviates the pain or improves the activity of KOA patients, the objective adverse reactions and high costs of these drugs are still key problems that need to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a systematic review published in 2013, KT interventions are not recommended for these clinical populations with musculoskeletal conditions (Parreira Pdo et al, 2014). However, other three meta-analyses find that KT can reduce pain and enhance knee function when compare to sham KT (Lu et al, 2018;Ouyang et al, 2018;Melese et al, 2020). Lin et al points out that KT versus physical therapy has substantial impact on pain and function alleviation in 2020 (Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Once we looked up the review articles on KT published over the past 5 years through the Medical Literature Analysis and Retrieval System Online (MEDLINE) (accessed via PubMed), a total of 52 studies were identified. Most of 52 studies are on cerebral palsy [13][14][15], low back pain [16][17][18][19][20][21][22][23], ankle functional performance [24][25][26], knee osteoarthritis (OA) [27][28][29][30][31][32][33], shoulder pain and disability [34][35][36][37][38], breast lymphedema [7,39], rehabilitation after stroke [40][41][42] and so on; however, there are only four studies related to edema [43][44][45][46]. Therefore, the purpose of this study was to review the literature on KT for reducing edema caused by musculoskeletal disorders and investigate whether the use of KT have any effects on controlling edema.…”
Section: Introductionmentioning
confidence: 99%